INNOVATION AS A CORPORATE STRATEGY IN ACHIEVING BUSINESS SUCCESS - Sigit Djalu Purwoko (SEAN Institute, 2023)
In the era of globalization and increasingly fierce competition, companies need to adopt innovative approaches and appropriate strategies to maintain and improve their performance. This study aims to analyze the role of innovation and corporate strategy in determining business success. The research method used is literature analysis, which involves studying works that are relevant to this topic. The data collected was analyzed qualitatively descriptive. The results of the study show that innovation is an important factor in business success in the modern competitive era. Innovation drives business growth by creating new products or services and increasing operational efficiency. In addition, innovation allows companies to stay relevant by adapting to market and technological changes. Innovation is also a strong differentiator for companies in creating added value and unique customer experiences. However, inappropriate strategies and innovations can result in risks of failure, inefficient spending, and market mismatch. Therefore, good innovation management is the key to achieving long-term success for the business.